The effectiveness of mobile app usage in facilitating weight loss: An observational study - Rosemary Huntriss; Rodion Salimgaraev; Dimitri Nikogosov; John Powell; Krista A. Varady (Wiley, 2024)
Abstract Aim With increasing rates of global obesity and associated health issues, there is an ever‐increasing need for weight management solutions to be more accessible. Mobile applications offer accessible support systems and have the potential to offer a viable and effective weight management solution as an alternative to traditional healthcare models. Objective To evaluate the effectiveness of the SIMPLE mobile application for time‐restricted eating in achieving weight loss (WL). Methods User data were analyzed between January 2021 and January 2023. In‐app activity was calculated as the proportion of active days over 12, 26 and 52 weeks. A day is considered active if it contains at least one in‐app action (e.g., logging weight, food, fasting, or physical activity). Users were categorized into four in‐app activity levels: inactive (in‐app activity <33%), medium activity (33%-66%), high activity (66%-99%), and maximal activity (100%). Weight change among in‐app activity groups was assessed at 12, 26, and 52 weeks. Results Out of 53,482 users, a positive association was found between the use of the SIMPLE app and WL. Active app users lost more weight than their less active counterparts. Active users had a median WL of 4.20%, 5.04%, and 3.86% at 12, 26, and 52 weeks, respectively. A larger percentage of active users-up to 50.26%-achieved clinically significant WL (≥5%) when compared to inactive users. A dose‐response relationship between WL and app usage was found after adjusting for gender, age, and initial Body Mass Index; a 10% increase in app activity correlated with increased WL by 0.43, 0.66 and 0.69 kg at 12, 26, and 52 weeks, respectively. Conclusions The study demonstrates that the SIMPLE app enables effective WL directly associated with the level of app engagement. Mobile health applications offer an accessible and effective weight management solution and should be considered when supporting adults to lose weight.